3c+7+12c=53

Simple and best practice solution for 3c+7+12c=53 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3c+7+12c=53 equation:


Simplifying
3c + 7 + 12c = 53

Reorder the terms:
7 + 3c + 12c = 53

Combine like terms: 3c + 12c = 15c
7 + 15c = 53

Solving
7 + 15c = 53

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + 15c = 53 + -7

Combine like terms: 7 + -7 = 0
0 + 15c = 53 + -7
15c = 53 + -7

Combine like terms: 53 + -7 = 46
15c = 46

Divide each side by '15'.
c = 3.066666667

Simplifying
c = 3.066666667

See similar equations:

| 32+n+n=126 | | 36x^2y-18xy^2+2y^3= | | -31/2x=14 | | m-5m-8=3+(-7)+m | | 4x-10=-6x+3 | | (N+4)*5=65 | | 79-(5x+16)=5(x+6)+x | | g(x)=2x-1 | | 3x^2-17x-12=0 | | 4x-7=3(2+1) | | 6:?x10/2 | | 9-4x[3-(7-2)/2] | | 8X(2X-3)-4X(4x-1)=40 | | 8x+6y=4 | | 100a-a^2-2484=0 | | 10m+6=56 | | 1-8x-7x=16 | | 4x-8=2x+19 | | 0.75y=9 | | 4x^2+9x^2=0 | | 4x*7/12x | | 2x^3+24x=y | | 42x^2-33x=0 | | 3v^5-192v^2= | | 7(-6x-4)= | | 3ln(4x-1)=9 | | ln(2x+1)+ln(x-3)=ln(x+5) | | 2x-8=38 | | 1=x/9 | | 9=-6+5v | | 0.3=20 | | x^2-8x+y^2+10y=-1 |

Equations solver categories